Mental Health Manpower and the Psychiatric Technician - National Association of Psychiatric Technology, Sacramento, CA.; California Society of Psychiatric Technicians, Sacramento; National Association of Psychiatric Technology, Sacramento, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
Dynamic changes are taking place in the field of mental health care which have a great effect on those people who provide the primary services of patient care, rehabilitation, and training. In recognition of these changes, the National Association of Psychiatric Technology selected "Mental Health Manpower and the Psychiatric Technician" as the theme for its annual convention in 1967. This report presents six articles which represent a selected digest of the proceedings from the Fresno Convention. These are "Mental Health: the Dynamics of Revolution,""Mental Health Manpower in Transition," a symposium on Federal and state regulations of nursing services, "Legal Aspects of Utilization of Psychiatric Technicians in Mental Health Services,""Private Psychiatric Hospitals," and"Programming for the Future." A curriculum report is appended. (BC)
Availability: National Association of Psychiatric Technology, 1127 11th Street, Sacramento, California 95814 ($2.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Design; Legal Problems; Programing; Psychiatric Hospitals; Allied Health Occupations; Conference Reports; Mental Health; Psychiatric Aides; California